KEBIJAKAN PEMBUKTIAN INSIDER TRADING PADA PASAR MODAL DI INDONESIA - Wibawa, I Gusti Lanang Agung Arya (Kerta Dyatmika, 2024)
Insider trading constitutes one of the most challenging forms of crime in the capital market due to the high level of difficulty in its evidentiary process. This offense falls under the category of white collar crime, characterized by complex and often undetectable modus operandi. This research aims to analyze the legal policies governing the evidentiary process of insider trading in Indonesia's capital market, as well as to identify the obstacles encountered in proving such offenses. This study adopts a normative legal research method, employing statutory and case study approaches. The findings indicate that the prohibition of insider trading was initially introduced through Minister of Finance Decree No. 1548/KMK/013/1990, and later reinforced by Law No. 8 of 1995 concerning the Capital Market (UUPM). The UUPM regulates the enforcement of insider trading provisions through administrative, civil, and criminal channels. Proof of insider trading is pursued by detecting the involvement of insiders conducting transactions based on material non-public information, and examining parties suspected of committing the offense. However, several obstacles to proving insider trading remain, including the complexity of the modus operandi, the lack of criminal history among offenders, and the difficulty of quantifying and proving actual losses before the court. The study concludes that, although the legal framework for proving insider trading in Indonesia is in place, its enforcement remains significantly hindered. Therefore, it is necessary to strengthen investigative mechanisms and inter-agency coordination to enhance accountability in the capital market.